Factorize the following:


Factorize the following:
a4b − 3a2b2 − 6ab3


The greatest common factor of the terms $a^{4} b, 3 a^{2} b^{2}$ and $6 a b^{3}$ of the expression $a^{4} b-3 a^{2} b^{2}-6 a b^{3}$ is $a b$.

Also, we can write $a^{4} b=a b \times a^{3}, 3 a^{2} b^{2}=a b \times 3 a b$ and $6 a b^{3}=a b \times 6 b^{2}$.

$\therefore a^{4} b-3 a^{2} b^{2}-6 a b^{3}=a b \times a^{3}-a b \times 3 a b-a b \times 6 b^{2}$

$=a b\left(a^{3}-3 a b-6 b^{2}\right)$

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now